2014
DOI: 10.7603/s40730-014-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine induced killer cell immunotherapy in cancer treatment: from bench to bedside

Abstract: Abstract-Cytokine-induced killer (CIK) cells are T effector cells generated by monocytes cultured and stimulated by cytokines. CIK cells were studied for more than 20 years ago. They can cause lysis of tumor cells that of both autologous and allogeneic origins, so that they were used in cancer treatment. This review aimed to summarize advancements of CIK cells and their current clinical applications in cancer treatment. In general, CIK cells were widely clinically used for recent 5 years. They gave promising r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Generally, anti-angiogenic effects are modulated through multiple pathways. The key signalling pathway that modulates proliferation of endothelial cells is the vascular endothelium growth (50)(51)(52)(53)(54). In this study, CIK cells were generated by culturing peripheral blood monocytes isolated from healthy donors with interferon-gamma (IFN-) and interleukin-2.…”
Section: Anti-cancermentioning
confidence: 99%
“…Generally, anti-angiogenic effects are modulated through multiple pathways. The key signalling pathway that modulates proliferation of endothelial cells is the vascular endothelium growth (50)(51)(52)(53)(54). In this study, CIK cells were generated by culturing peripheral blood monocytes isolated from healthy donors with interferon-gamma (IFN-) and interleukin-2.…”
Section: Anti-cancermentioning
confidence: 99%
“…The obtained CIK cells are heterogeneous lymphocytes, in which over 90% are CD3 + cells, and can be divided into two main subsets: CD3 + CD56 + cells and CD3 + CD56 ‐ T cells . Due to the limited initial number, CIK cells need to be expanded ex vivo up to 10 10 cells per infusion to meet the clinical requirements . Moreover, it was reported that the clinical response was related to injected cell numbers; therefore, it is necessary to optimize the ex vivo CIK cells expansion process for better clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…9 The obtained CIK cells are heterogeneous lymphocytes, in which over 90% are CD3 + cells, and can be divided into two main subsets: CD3 + CD56 + cells and CD3 + CD56 -T cells. [14][15][16] Moreover, it was reported that the clinical response was related to injected cell numbers [17][18][19] ; therefore, it is necessary to optimize the ex vivo CIK cells expansion process for better clinical efficacy. [14][15][16] Moreover, it was reported that the clinical response was related to injected cell numbers [17][18][19] ; therefore, it is necessary to optimize the ex vivo CIK cells expansion process for better clinical efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The qualifier "cytokine-induced killer" indicates that they are generated via administration of cytokines during in vitro culture (Arafar, 2014;Linn and Hui, 2010). Cells which have the most potential effector function in CIK culture coexpress CD3 and CD56 surface molecules; possess a potent, MHC-unrestricted tumor-killing ability; and significantly reduced alloreactivity (Sangiolo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%